2015
DOI: 10.1002/2015jc011033
|View full text |Cite
|
Sign up to set email alerts
|

Eddy‐topography interactions and the fate of the Persian Gulf Outflow

Abstract: The Persian Gulf feeds a warm and salty outflow in the Gulf of Oman (northern Arabian Sea). The salt climatological distribution is relatively smooth in the Gulf of Oman, and the signature of a slope current carrying salty waters is difficult to distinguish hundreds of kilometers past the Strait of Hormuz, in contrast to other outflows of the world ocean. This study focuses on the mechanisms involved in the spreading of Persian Gulf Water (PGW) in the Gulf of Oman, using a regional primitive equation numerical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 53 publications
6
40
0
Order By: Relevance
“…Notice that the annual EKE over the whole domain is higher in ROMS than in Aviso by ∼ 20% (Fig. 3 in Vic et al 2015).…”
Section: Surface Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that the annual EKE over the whole domain is higher in ROMS than in Aviso by ∼ 20% (Fig. 3 in Vic et al 2015).…”
Section: Surface Circulationmentioning
confidence: 99%
“…Bottom stress is linear with a drag coefficient C d = 3 × 10 −4 m s −1 . Additional information is in Vic et al (2015).…”
Section: Regional Ocean Modelmentioning
confidence: 99%
“…Other generation mechanisms exist for anticyclonic SCVs like the instability of a coastal undercurrent [D'Asaro, 1988b;Molemaker et al, 2015] or the interaction of large-scale eddies with the topography [Vic et al, 2015]. In the NW Mediterranean Sea, the first mechanism has been identified to be important along the northwestern part of Sardinia leading to the formation of ''Suddies'' characterized by warm and salty LIW .…”
Section: 1002/2016jc012144mentioning
confidence: 99%
“…In June 2011, anticyclone A3 was advected northward as the summer monsoon began, thus reducing the deformation field off Ra's Al Hamra. To break the PGW outflow into lenses and filaments, Vic et al (2015), using a highresolution numerical model, showed that a strong shear and strain is necessary. Thus fewer submesoscale PGW structures are expected to be observed during the summer monsoon (when the deformation field is less intense), but due to a lack of regular observations at the depth of PGW.…”
Section: Recurrence Of Pgw Lensesmentioning
confidence: 99%